Method for exploring intrinsic defects of semi-Heusler alloy
Through first-principle calculation and thermodynamic analysis, the defect type and concentration of semi-Hasler alloy were determined, which solved the problem of optimization of thermoelectric material performance, realized theoretical research and prediction of intrinsic defects of thermoelectric material, and improved the reliability of performance prediction of thermoelectric material.
Patent Information
- Application Number
- CN202311170898.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-12
AI Technical Summary
The thermoelectric conversion efficiency of existing thermoelectric materials is low and costly, so they cannot be used in batches. Due to the low concentration and complexity of defects, it is difficult to effectively analyze and optimize through experimental methods.
Through first-principle calculation combined with thermodynamic analysis, the perfect and defective supercells of semi-Hasler alloy are determined, the relationship between defect formation energy and Fermi energy level is analyzed, the main intrinsic defect types are judged, and the defect concentration, electronic structure and chemical bonds are predicted and analyzed.
A systematic theoretical study on the intrinsic defects of half-Hasler alloy was achieved, providing theoretical guidance for the optimization performance of thermoelectric materials, and predicting the electric transport types of different compounds was obtained, which was reliable compared with the experiment.
Smart Images

Figure CN119626393A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermoelectric materials, in particular to a method for exploring intrinsic defects of semi-Heusler alloys. Background Art
[0002] More than 80% of the world's electricity supply still relies on fossil fuels, which provide a lot of power for heat engines. However, the conversion efficiency of heat engines is only 30%, so a lot of heat is lost as waste heat. Thermoelectric (TE) technology can directly convert waste heat into useful electrical energy and can be used to improve efficiency and save energy. Due to its solid-state characteristics, thermoelectric technology has many advantages such as zero emissions and low noise. In recent years, with people's renewed attention to environmental issues, the development prospects of converting waste heat into useful electrical energy have become increasingly broad, and the term thermoelectric has aroused great interest. From electric vehicles to wearable devices to space exploration, the prospect of reducing energy demand seems to be just around the corner. Although the research on thermoelectric materials has made certain progress in the past decade of exploration. However, due to its general thermoelectric conversion efficiency and relatively high cost, it is impossible to realize the mass application of thermoelectric materials. Optimizing thermoelectric performance mainly involves regulating two aspects: electrical transport performance and thermal transport performance, hoping to obtain materials with high electrical conductivity, high Seebeck coefficient and low thermal conductivity. However, due to the mutual coupling between thermoelectric parameters, there are several well-known difficulties in optimizing thermoelectric performance.
[0003] Generally speaking, in the actual preparation process of crystals, defects of different concentrations will inevitably be generated. The presence of defects in the material will cause changes in the volume, structure and other aspects of the material, which will have a great impact on the electrical, optical, magnetic, mechanical and other properties. Thermoelectric materials are generally narrow-bandgap semiconductor materials, and their thermoelectric properties are difficult to optimize, which restricts its development. To improve the thermoelectric performance, one is to optimize in the direction of electrical transport, mainly the optimization of carrier concentration; the other is to optimize in the direction of thermal transport, mainly the optimization of thermal conductivity. The significance of reasonable control of defects in crystals in optimizing thermoelectric performance cannot be underestimated, because defects in crystals will have a certain impact on the properties of materials such as carrier concentration, carrier mobility, and thermal conductivity. However, it is difficult to effectively analyze the properties of defects in materials by experimental methods because the defect concentration in actual materials is often very low. Summary of the invention
[0004] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the existing technology and provide a method for exploring the intrinsic defects of semi-Heusler alloys. By reasonably controlling the system defects, a systematic theoretical study of the defect properties of the material is carried out through first-principles calculations combined with thermodynamic analysis, providing a theoretical basis for the defect properties of semi-Heusler alloy materials.
[0005] One of the purposes of the present invention is to provide a technical solution for exploring the intrinsic defects of semi-Heusler alloys, specifically:
[0006] A method for exploring intrinsic defects of a semi-Heusler alloy comprises the following steps:
[0007] S1. Determine the perfect supercell and defective supercell of the compound of semi-Heusler alloy;
[0008] S2. determining the chemical potential range of the perfect supercell;
[0009] S3, using first principle software to perform theoretical calculations on the perfect supercell and the defective supercell respectively to obtain defect formation energy;
[0010] S4. Determine the Fermi levels of the perfect supercell and the defect supercell, and analyze the relationship between the defect formation energy and the Fermi level, thereby determining the type of main intrinsic defects in the compound.
[0011] Preferably, the defective supercell is a crystal structure in which any one of defects selected from vacancies, gaps, antisites, substitutions and doping is provided in the perfect supercell.
[0012] Preferably, the formation enthalpy of the impurity phase composed of relevant elements in the compound is analyzed, and the chemical potential range of the perfect supercell is determined accordingly.
[0013] Preferably, the formation energy of the defect is the difference between the total energy of the defect supercell and the total energy of the perfect supercell.
[0014] Preferably, the method of determining the type of the main intrinsic defect is that in the same range of the Fermi level, the defect corresponding to a relatively low formation energy of the defect is the main intrinsic defect type in the compound.
[0015] The second object of the present invention is to provide a technical solution for a method for predicting defect concentration of a semi-Heusler alloy with intrinsic defects, specifically:
[0016] A defect concentration prediction method for a semi-Heusler alloy with intrinsic defects uses a defect supercell of a compound of a semi-Heusler alloy with major intrinsic defects for first-principles calculation to calculate the thermal equilibrium carrier concentration and the defect concentration.
[0017] The third object of the present invention is to provide a technical solution for a method for predicting the electronic structure of a semi-Heusler alloy with intrinsic defects, specifically:
[0018] A method for predicting the electronic structure of a semi-Heusler alloy with intrinsic defects is to calculate the electronic energy bands of a defect supercell of a compound of a semi-Heusler alloy with major intrinsic defects using first principles to obtain the electronic structure.
[0019] The fourth object of the present invention is to provide a technical solution for a method for analyzing chemical bonds of a semi-Heusler alloy with intrinsic defects, specifically:
[0020] A method for analyzing chemical bonds of a semi-Heusler alloy with intrinsic defects is to apply first principles to calculate the differential charge density and crystal orbital Hamiltonian population (-COHP) curve of a defect supercell of a compound of a semi-Heusler alloy with major intrinsic defects, and analyze the chemical bonds according to the calculation results.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a method for exploring the intrinsic defects of a semi-Heusler alloy. First, defects are introduced into a compound, and then theoretical calculations are performed using a first-principles method. The main intrinsic defects are determined by analyzing the relationship between the formation energy of the defects and the Fermi level. Based on this, theoretical analysis of properties such as defect concentration, electronic structure, and the relationship between defects and chemical bonds is performed again. The intrinsic defects of thermoelectric materials are studied from the direction of theoretical calculation, and prediction results of different electrical transport types of different compounds are obtained. Compared with experiments, the method is reliable and can provide theoretical predictions for unknown new materials.
[0023] The present invention also provides a method for predicting or analyzing the defect concentration, electronic structure, chemical bonds, etc. of a semi-Heusler alloy with intrinsic defects, providing a theoretical guidance direction for thermoelectric materials to achieve optimized performance by means of reasonable control of system defects, and providing new insights into optimizing thermoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A flow chart of the method for exploring intrinsic defects of semi-Heusler alloys in the present invention;
[0025] Figure 2 The crystal structure diagram of the compound of the semi-Heusler alloy in the present invention ( Figure 2 (a)) and schematic diagram of all defect types ( Figure 2 (b));
[0026] Figure 3 is the chemical potential range when the six compounds in the present invention exist stably, wherein point M represents A-poor, point N represents B-poor, point C represents A-rich, and point D represents B-rich;
[0027] Figure 4 M in the present invention IV NiSn(M IV =The relationship between the intrinsic defect formation energy and the Fermi level of three compounds (Zr, Ti, Hf);
[0028] Figure 5 M in the present invention III NiSb(M III =Y, Sc, Er) three compounds intrinsic defect formation energy and Fermi level relationship diagram;
[0029] Figure 6 is a graph showing the relationship between carrier concentration and temperature of six compounds in the present invention;
[0030] Figure 7 is the carrier concentration of the main defects in the six compounds when the temperature changes from 300K to 1200K ( Figure 7 (a)) and main defect concentration ( Figure 7 (b));
[0031] Figure 8 The Ni i Defective M IV NiSn(M IV =Zr, Ti, Hf) and with V Ni Defective M III NiSb(M III =Y, Sc, Er) energy band electronic structure of the compound;
[0032] Fig. 9 The differential charge density diagram of TiNiSn and ScNiSb and the -COHP and -ICOHP (dashed line) curves;
[0033] Fig.10 The differential charge density diagram of ZrNiSn and YNiSb and the -COHP and -ICOHP (dashed line) curves;
[0034] Fig.11 The differential charge density diagram of HfNiSn and ErNiSb, as well as the -COHP and -ICOHP (dashed line) curves. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] For ease of understanding, the abbreviations or nouns mentioned below are first explained:
[0037] ABC: abbreviation of semi-Heusler structure compound, where A represents two types of elements, M IV (Zr, Ti or Hf elements) and M III (Y, Sc, or Er element), B represents Ni element, and C represents Sn or Sb element.
[0038] The following is an introduction to a specific implementation of a method for exploring intrinsic defects in semi-Heusler alloys.
[0039] A method to explore the intrinsic defects of semi-Heusler alloys, such as Figure 1 As shown, it includes the following four steps:
[0040] In the first step, a supercell of a perfect crystal structure without defects (perfect supercell) and a crystal supercell structure containing defects (defective supercell) of a semi-Heusler alloy compound (hereinafter referred to as compound) are determined.
[0041] In this embodiment, the perfect supercell is a 2×2×2 supercell structure of a perfect crystal structure.
[0042] In this embodiment, the defect supercell is a 2×2×2 supercell structure of a perfect crystal structure, and contains defects inside. The types of defects include: vacancies, gaps, anti-sites, substitutions, and doping.
[0043] Specifically, the types of defects include: a vacancy defect of an A, B or C atom (denoted as V A 、V B or V C ), adding a B atom (denoted as B i ), exchange the positions of atoms of two different elements (denoted as Anti, for example, Anti(AB) represents an A atom exchanging positions with a B atom), displacement of a B atom (for example, a B atom moves from the 4c position to the 4d position, denoted as B -dis ).
[0044] In this embodiment, the specific defects are as follows: Figure 2 As shown, it should be noted that Figure 2 Schematic diagram of all types of crystal defects. In actual calculations, only one type of defect is included in the supercell structure.
[0045] In the second step, the chemical potential range of the perfect supercell of the compound is determined.
[0046] Furthermore, the impurity phase is analyzed and the chemical potential range of the perfect supercell of the compound is determined accordingly.
[0047] Specifically, since the chemical potential of an element affects the intrinsic defect formation energy, three thermodynamic limits are used to analyze impurity phases such as simple elements and binary phases to determine the stable chemical potential range when the impurity-free phase is formed.
[0048] In this embodiment, ZrNiSn is taken as an example to introduce the method of determining the range of stable chemical potential:
[0049] (1) The sum of the elemental chemical potentials of the component elements should be equal to the formation enthalpy of the compound, that is:
[0050] μ Zr +μ Ni +μ Sn =ΔH f (ZrNiSn)
[0051] Where ΔH f (ZrNiSn) is the formation enthalpy of ZrNiSn.
[0052] (2) The chemical potential range is further limited by the second phase formation energy, such as ZrNi3, Zr5Sn3 and Ni3Sn4, which are described as follows:
[0053] μ Zr +3μ Ni <ΔH f (ZrNi3)
[0054] 5μ Zr +3μ sn <ΔH f (Zr5Sn3)
[0055] 3μ Ni +4μ Sn <ΔH f (Ni3Sn4)
[0056] (3) All component elements must play a positive role in the existence of the compound, and no single substance can be generated, that is:
[0057] μ Zr <0
[0058] μ Ni <0
[0059] μ Sn <0
[0060] Where μ represents the chemical potential of an element, ΔH f Represents the enthalpy of formation of a compound.
[0061] When the ZrNiSn compound exists stably, that is, there is no impurity phase, the following conditions must be met: (1) the phase exists stably, (2) the single component will not exist stably, and (3) the competing second phase is unstable. Therefore, the chemical potential range of the ZrNiSn compound when it exists stably is as follows: Figure 3 As shown in the gray part in (a), only the most competitive impurity phase is shown in the figure. Outside the gray part surrounded by different lines, there is the influence of the competing impurity phase, while inside the gray part, the ZrNiSn structure can exist stably.
[0062] Similarly, for compounds TiNiSn, HfNiSn, YNiSb, ScNiSb and ErNiSb, the chemical potential ranges of the perfect supercell when they are stable are as follows: Figure 3 (b) to (f).
[0063] Figure 3 In each figure, the four points M, N, C, and D correspond to four different chemical potentials, A-poor, B-poor, A-rich, and B-rich, respectively, to analyze the intrinsic defect formation energy of the compound.
[0064] The third step is to use the first-principles software to perform theoretical calculations on the perfect supercell and the defective supercell respectively to obtain the formation energy of a certain defect.
[0065] Furthermore, the expression of defect formation energy is:
[0066]
[0067] Among them, i represents the defect, E pefect is the total energy of the perfect supercell, is the total energy of the defect supercell, n i is the number of defects in the unit cell, μ i is the chemical potential of the defect element in the unit cell, q i is the charge carried by the defective supercell, E F is the Fermi level, E V is the energy of the valence band top (VBM), and ΔV is the electrostatic potential difference generated when the VBM of the defective supercell is aligned with that of the perfect supercell.
[0068] The fourth step is to determine the Fermi levels of the perfect supercell and defect supercell of the compound, and analyze the relationship between the defect formation energy of the compound and the Fermi level, thereby judging the main intrinsic defect type in the compound (referred to as the main defect, or the most stable defect).
[0069] Specifically, the relationship between the defect formation energy and the Fermi level of the six compounds under four chemical potential conditions: A-poor, B-poor, A-rich, and B-rich is shown in the following figure: Figure 4 and Figure 5 As shown, Figure 4 (a) to (c) correspond to ZrNiSn, TiNiSn, HfNiSn, Figure 5 (a) to (c) YNiSb, ScNiSb, ErNiSb, where the gray part represents the range of the Fermi level from 300K to 1200K, and the red arrow represents the band gap of the system. It can be seen that although the intrinsic defect formation energies of these six common compounds are different, the main intrinsic defect types are Ni interstitial and Ni vacancy. IV NiSn(M IV =Zr, Ti, Hf) series compounds, generally Ni i is the main defect, and M III NiSb(M III =Y, Sc, Er) compounds tend to form V Ni defect.
[0070] The following provides an introduction to a specific implementation of a method for predicting defect concentration of a semi-Heusler alloy with intrinsic defects using the main intrinsic defect types in the compound obtained by the method for exploring intrinsic defects of a semi-Heusler alloy provided above.
[0071] A defect concentration prediction method for a semi-Heusler alloy with intrinsic defects, the steps are as follows:
[0072] The defect supercells corresponding to the main intrinsic defect types of the six compounds are used to calculate the thermal equilibrium carrier concentration (Defect concentration) and defect concentration (Defect concentration) of the defect supercells of the compounds.
[0073] Thermal equilibrium carrier concentration n e =C e -C h The expression is:
[0074] in,
[0075] Defect concentration n h The expression is:
[0076] in,
[0077] Among them, C e is the electron concentration, C h is the hole concentration, N C and N Vare the effective state density of the conduction band and the valence band, respectively, k is the Boltzmann constant, T is the temperature, ε f is the Fermi level, E g is the band gap value, is the effective mass of the electron at the bottom of the conduction band, is the effective mass of the hole at the top of the valence band, and h is Planck's constant.
[0078] In this example, the relationship between the carrier concentration and temperature of six compounds at four different chemical potentials at different temperatures was calculated and compared with the experimental values, such as Figure 6 As shown in the figure, Ref
[45] represents the reference Chemistry of Materials, 2017, 29(3): 1156-64., Ref
[46] represents the reference Energy and Environmental Science, 2016, 9(1): 155-63., Ref
[47] represents the reference Advanced Energy Materials, 2019, 10(11): 11-14., Ref
[48] represents the reference Journal of Materials Chemistry A, 2017, 5(10): 5098-105., Ref
[49] represents the reference Science (New York, NY), 2008, 320(5876): 634-638., and Ref
[50] represents the reference Solid State Electronics, 1961, 11(9): 833-868.
[0079] Figure 6 The experimental values in the table are from the corresponding references, and the test conditions are 300K. By comparing the theoretical data with the experimental data, it is found that the intrinsic defects in the compound will cause changes in the carrier concentration, which in turn affects the electrical transport properties. IV NiSn(M IV =Zr, Ti, Hf) series compounds, (1) the electron concentration is greater than the hole concentration, showing n-type transport properties, and the carrier concentration reaches the maximum value under Ni-rich chemical potential conditions, (2) under Ni-rich conditions, at 1000K, the maximum carrier concentration reaches 10 18 -10 19 cm -3 For M III NiSb(M III=Y, Sc, Er) compounds, (1) the hole concentration is greater than the electron concentration, showing p-type transport properties, and the carrier concentration reaches a maximum at the Ni-poor chemical potential. (2) For ScNiSb, under Ni-rich conditions, the difference between electrons and holes is positive because Ni i Has the lowest defect formation energy, such as Figure 6 (e) This results in weak n-type transport, (3) due to p-type defects V Ni , the maximum carrier concentration of YNiSb reaches 1.0×10 20 cm -3 , at 300K, the carrier concentration of YNiSb (~10 19 cm -3 ) and experimental value (~3.0×10 19 cm -3 )(From reference Intermetallics, 2019, 108: 55-60.) Under Ni-poor conditions, the maximum carrier concentration of ScNiSb reaches 2.5×10 19 cm -3 The maximum carrier concentration of ErNiSb reaches 5.9×10 19 cm -3 .
[0080] Figure 7 is the concentration of the main defects of the six compounds at different temperatures (Ni i In M IV NiSn(M IV =Zr, Ti, Hf dominate, V Ni In M III NiSb(M III =Y, Sc, Er) dominates), at 300K, Ni in ZrNiSn i The maximum value is 0.017%, Ni in TiNiSn i The maximum value is 0.063%, Ni in HfNiSn i The maximum value is 0.006%. The five-pointed star in the figure represents the published experimental value. The calculated defect concentration is slightly lower than the experimental value. This is because only the concentration of a single defect is calculated in this embodiment. In reality, at lower temperatures, there is not a single defect in the compound. At high temperatures, V Ni The maximum acceptor defect concentrations increase to 1.87%, 0.24% and 1.16% in YNiSb, ScNiSb and ErNiSb, respectively, which are very close to the experimental values.
[0081] The following is an introduction to a specific implementation of a method for predicting the electronic structure of a semi-Heusler alloy with intrinsic defects using the main intrinsic defect types in the compound obtained by the method for exploring the intrinsic defects of a semi-Heusler alloy provided above.
[0082] A method for predicting the electronic structure of a half-Heusler alloy with intrinsic defects, comprising the following steps:
[0083] The electronic band structures of the six compounds are calculated by using defect supercells corresponding to their respective main intrinsic defect types, such as Figure 8 As shown, the calculation results show that: M IV NiSn(M IV =Zr, Ti, Hf) in Ni i Defects cause local impurity bands that reduce the band gap and increase the carrier concentration. The presence of these impurity bands can also explain the M IV NiSn(M IV =Zr, Ti, Hf) The most stable defect at the equilibrium Fermi level is Ni with a positive divalent i (2+); M III NiSb(M III =Y, Sc, Er) does not have V Ni Impurity state caused by V Ni No impurity state is generated, M III NiSb(M III =Y, Sc, Er) The most stable defect in the equilibrium Fermi level is the uncharged V Ni (0).
[0084] The following is an introduction to a specific implementation of a method for analyzing chemical bonds of a semi-Heusler alloy with intrinsic defects using the main intrinsic defect types in a compound obtained by the above-mentioned method for exploring intrinsic defects in a semi-Heusler alloy.
[0085] A method for analyzing chemical bonds of a semi-Heusler alloy with intrinsic defects, the steps are as follows:
[0086] The differential charge density and crystal orbital Hamiltonian population (-COHP) curves were calculated for the defect supercells corresponding to the main intrinsic defect types in the six compounds.
[0087] The calculation results of differential charge density are as follows: Figures 9 to 11 As shown, red and blue represent gain and loss of electrons, respectively.
[0088] Fig. 9 (a) and (b) show the charge density difference around Ni atoms in the perfect supercells of TiNiSn and ScNiSb, respectively; Fig. 9(d) and (e) show the calculated Ni i The charge density difference around the interstitial Ni atoms in the defect supercell is shown in Figure 1. It can be seen that in the perfect supercell, the Ni-Ti chemical bond in TiNiSn is stronger than the Ni-Sc in ScNiSb; similarly, in the case of the Ni i In the defect supercell of the defect, Ni in TiNiSn i -Ti's bonding is still stronger than Ni in ScNiSb i -Sc strong.
[0089] from Fig.10 and Fig.11 It can also be seen that in the perfect supercell, the chemical bond of the Ni-Zr pair in ZrNiSn is stronger than that of the Ni-Y pair in YNiSb, and the chemical bond of the Ni-Hf pair in HfNiSn is stronger than that of the Ni-Er pair in ErNiSb; i In the defect supercell of the defect, Ni in ZrNiSn i -Zr has a stronger chemical bond than Ni in YNiSb i -Y pair, Ni in HfNiSn i The chemical bond of the -Hf pair is stronger than that of Ni in ErNiSb i -Er pair. This indicates that such strong interatomic interactions are more conducive to the formation of defects in the lattice by interstitial Ni atoms.
[0090] M in the perfect supercells of six compounds IV (M III )-Ni pairs and M in defective supercells IV (M III )-Ni i The crystal orbital Hamiltonian population (-COHP) curve is as follows: Figures 9 to 11 As shown,
[0091] Taking TiNiSn and ScNiSb as examples, Fig. 9 The Ni-Ti bond in the TiNiSn perfect supercell (c) shows a higher -COHP curve than the Ni-Sc bond in the ScNiSb perfect supercell, indicating that the Ni-Ti pair has a stronger bond strength. The COHP integral at the Fermi level position (-ICOHP, Fig. 9The dashed line in (c) can quantitatively determine the strength of the bond. The -ICOHP value of the Ti-Ni pair is as high as 1.67 eV / pair, while the -ICOHP value of the Sc-Ni pair in ScNiSb is 1.44 eV / pair, indicating a stronger bonding strength between Ti and Ni. Because the atoms in the crystal vibrate around the lattice point in the equilibrium position, when the chemical bond between an atom and its surrounding atoms is weak, the atom is likely to be excited and deviate from the normal equilibrium position, resulting in a vacancy defect. On the contrary, if an atom forms a strong chemical bond with the atoms around it, the atom may exist stably in the crystal. Therefore, the energy required to form a vacancy in ScNiSb is lower than that in TiNiSn, so it is more inclined to form a V Ni This phenomenon well verifies the above-mentioned carrier concentration prediction method and experimental observation of a semi-Heusler alloy with intrinsic defects.
[0092] for Fig. 9 (f) shows Ni i Defect supercell of defects, Ni in TiNiSn i -Ti bonding is still better than Ni in ScNiSb i -Sc is more stable. Ni i The -ICOHP value of the -Ti pair is as high as 1.28 eV / pair, while the Ni i The ICOHP of the Ni-Sc pair is 0.78 eV / pair, which indicates that the i -Ti pairs have stronger bonding strength. Nature will spontaneously develop towards the direction of stable existence of the system, and the interstitial Ni atoms will reduce the energy of the system, making it more stable. Fig.10 as well as Fig.11 As shown in the figure, we performed the same calculations for the other four compounds and the results show that, regardless of whether in a perfect supercell or a defective supercell, M IV NiSn(M IV = Zr, Ti, Hf) IV -Ni is stronger than M III NiSb(M III =Y, Sc, Er) III -You are right.
[0093] It should be noted that the six compounds of semi-Heusler alloys involved in this specific embodiment are from the MatHub-3d database.
[0094] It should be noted that the theoretical calculation of the semi-Heusler alloy involved in this specific embodiment is performed using the VASP program, with a plane wave energy cutoff of 350 eV and a convergence criterion of 10 -4eV, the lattice constant and ion position of the perfect supercell are fully optimized, and the relaxation criterion for each atom is Defective supercells containing defects are constructed using optimized perfect supercells, and for different defective supercells, the atomic positions are further relaxed without changing the lattice constants.
[0095] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention and do not violate the method for exploring intrinsic defects of semi-Heusler alloys of the present invention, they belong to the protection scope of the present invention.
Claims
1. A method for exploring intrinsic defects of semi-Heusler alloys, characterized in that: The steps include: S1. Determine the perfect supercell and defective supercell of the compound of semi-Heusler alloy; S2. determining the chemical potential range of the perfect supercell; S3, using first principle software to perform theoretical calculations on the perfect supercell and the defective supercell respectively to obtain defect formation energy; S4. Determine the Fermi levels of the perfect supercell and the defect supercell, and analyze the relationship between the defect formation energy and the Fermi level, thereby determining the type of main intrinsic defects in the compound.
2. The method for exploring intrinsic defects of semi-Heusler alloy according to claim 1, characterized in that: The defective supercell is a crystal structure in which any one of defects including vacancies, gaps, antisites, substitutions and doping is provided in the perfect supercell.
3. The method for exploring intrinsic defects of semi-Heusler alloy according to claim 1, characterized in that: The formation enthalpy of the impurity phase composed of the relevant elements in the compound is analyzed, and the chemical potential range of the perfect supercell is determined accordingly.
4. The method for exploring intrinsic defects of semi-Heusler alloy according to claim 1, characterized in that: The formation energy of the defect is the difference between the total energy of the defect supercell and the total energy of the perfect supercell.
5. The method for exploring intrinsic defects of semi-Heusler alloy according to claim 1, characterized in that: The method for determining the type of the main intrinsic defect is that in the same range of the Fermi level, the defect corresponding to a relatively low formation energy of the defect is the main intrinsic defect type in the compound.
6. A method for predicting defect concentration of a semi-Heusler alloy with intrinsic defects, characterized in that: A compound of a semi-Heusler alloy has main intrinsic defects determined by the method for exploring intrinsic defects of a semi-Heusler alloy as described in any one of claims 1 to 5, and a defect supercell of the compound with the main intrinsic defects is used for first-principles calculation to calculate the thermal equilibrium carrier concentration and the defect concentration.
7. A method for predicting the electronic structure of a semi-Heusler alloy with intrinsic defects, characterized in that: A compound of a semi-Heusler alloy has a main intrinsic defect determined by the method for exploring intrinsic defects of a semi-Heusler alloy as described in any one of claims 1 to 5, and the electronic energy band of the defect supercell of the compound with the main intrinsic defect is calculated using the first principles to obtain the electronic structure.
8. A method for analyzing chemical bonds of a semi-Heusler alloy with intrinsic defects, characterized in that: A compound of a semi-Heusler alloy has a main intrinsic defect determined by the method for exploring intrinsic defects of a semi-Heusler alloy as described in any one of claims 1 to 5, and a defect supercell of the compound with the main intrinsic defect is subjected to first-principles calculation of differential charge density and crystal orbital Hamiltonian population (-COHP) curve, and the chemical bond analysis is performed based on the calculation results.
Citation Information
Patent Citations
Method for calculating and regulating perovskite material defects based on first principle
CN111653325A
P-type Heusler-like structure thermoelectric material and preparation method thereof
CN116347970A
Method for high-throughput calculation of different-temperature electronic structures of semi-Heusler material
CN116759023A
Magnesium alloys having long-period stacking order phases
US20150086413A1
ZrCoBi Based Half Heuslers with High Thermoelectric Conversion Efficiency
US20210265549A1